(untitled) (Al-Aasar, 2025)
This research study conducts an in-depth examination of the political theories of state in Islam and Judaism, particularly in the light of divine scriptures, namely the Qur’an and the Torah, along with their associated jurisprudential and rabbinical traditions. The study analyzes how both religions established the principles of state, governance, law, and social order, and how religious commandments were implemented within political, legal, and social structures.In the Islamic conception of state, the notion of Divine Sovereignty (Hakimiyyat al-Ilahiyya) holds a central position, where God’s rule is harmonized with human caliphate (Khilafah) and consultation (Shura). Shariah is implemented as state law, emphasizing justice (Adl), equity, public welfare (Falah al-‘Amm), and obedience to legitimate authority (Ulu’l-Amr). The practical models of Medinan State and the Rashidun Caliphate operationalized this theory, ensuring that political, judicial, and administrative structures remain compliant with Shariah. In contrast, the Jewish conception of state is based on the Torah, Talmud, and rabbinical tradition. Here, Divine Sovereignty is linked with prophethood and the concept of a chosen nation (Am Yisrael). Mosaic Law (Shari’ah Musawi) and rabbinical law provide the foundations for governance, judiciary, and collective responsibility. The interrelation between kingship and prophecy, the concept of Promised Land (Eretz Ha-Mo’ed), and the adaptation of political principles during exile (Galut) play a crucial role in Jewish political thought. Relations with non-Jewish communities are regulated according to justice, legal principles, and moral responsibility. The comparative analysis demonstrates that Islam emphasizes human caliphate, consultation, and universalism, whereas Judaism prioritizes law, prophecy, and chosen nationhood as the foundation of governance. Both religions place central importance on justice, moral values, the supremacy of law, and the rights of non-Muslims, though differences exist in practical implementation and philosophical interpretation.This study provides a comprehensive scholarly framework for interfaith understanding, historical and theoretical analysis of political thought, and the role of religion in contemporary political and social structures. It concludes that both Islamic and Jewish models of governance integrate religious principles, legal frameworks, and moral values into a coherent system that ensures justice, equity, and collective welfare.